2008
DOI: 10.1517/17425240802583421
|View full text |Cite
|
Sign up to set email alerts
|

Applications of hot-melt extrusion for drug delivery

Abstract: In today’s pharmaceutical arena, it is estimated that more than 40% of new chemical entities produced during drug discovery efforts exhibit poor solubility characteristics. However, over the last decade hot-melt extrusion (HME) has emerged as a powerful processing technology for drug delivery and has opened the door to a host of such molecules previously considered unviable as drugs. HME is considered to be an efficient technique in developing solid molecular dispersions and has been demonstrated to provide su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
103
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(103 citation statements)
references
References 86 publications
0
103
0
Order By: Relevance
“…A myriad of techniques such as spray drying [2], solvent evaporation [3], nanocrystal formation [4], complexation [5], and micronization of active pharmaceutical ingredient (API) [6] have been widely utilized in the industry to improve the solubility and/or dissolution rate of such BCS class II drugs, thereby enhancing their bioavailability. During the past couple of decades, hot-melt extrusion (HME) technology has gained enormous interest among researchers for improving the bioavailability of drug substances, especially those having low water solubility, by the formation of solid dispersions [7][8][9]. Compared to other techniques, HME offers several advantages such as being solvent-free, a potentially continuous process, and involving fewer processing steps in general.…”
Section: Introductionmentioning
confidence: 99%
“…A myriad of techniques such as spray drying [2], solvent evaporation [3], nanocrystal formation [4], complexation [5], and micronization of active pharmaceutical ingredient (API) [6] have been widely utilized in the industry to improve the solubility and/or dissolution rate of such BCS class II drugs, thereby enhancing their bioavailability. During the past couple of decades, hot-melt extrusion (HME) technology has gained enormous interest among researchers for improving the bioavailability of drug substances, especially those having low water solubility, by the formation of solid dispersions [7][8][9]. Compared to other techniques, HME offers several advantages such as being solvent-free, a potentially continuous process, and involving fewer processing steps in general.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it also found its application in pharmaceutical manufacturing operations, offering many advantages compared to traditional pharmaceutical processing techniques [1][2][3][4][5] for solids: the process is anhydrous; poorly compactable materials can be incorporated into tablets; the materials have a short residence time in the extruder during processing; HME enables superior mixing (both distributive and dispersive); it allows the production of formulations with modified release; it allows masking of the bitter taste of several active pharmaceutical ingredients (API's) and in addition it improves the dissolution rate and the bioavailability of poorly water soluble drugs by the formation of solid solutions or solid dispersions [6] . A solid dispersion consists of at least two different components, generally a hydrophilic matrix and a hydrophobic drug [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Polymethacrylates are widely used in pharmaceutical delivery systems for sustained drug delivery, 10) hot melt extrusion, 11,12) microencapsulation, 13) nanoparticle, 14,15) antiretroviral drug delivery, 15,16) floating microspheres, 17) colon delivery 18,19) and transdermal drug delivery. 20) In our previous studies we showed the effect of thermal treating on the release of indomethacin 8) and diclofenac sodium 9) from acrylic matrix tablets and mechanistically studied the effect of heat-treating on physicochemical structure of tablet.…”
mentioning
confidence: 99%